Trade reform with a government budget constraint - Anderson, James E. 1943- (NBER working paper series, 1996)
The standard theory of trade reform uses a passive government budget constraint, in which changes in tariff revenue are offset by changes in lump sum transfers. This paper offers a general framework for the analysis of trade reform when the government budget constraint is active, meaning that tariff revenue cuts must be offset by distortionary fiscal policy changes --- public good supply cuts or alternative tax increases. Useful and simple new expressions characterizing welfare improving trade reform compare the Marginal Cost of Funds (MCF) of trade taxes with the MCF of consumption taxes. The MCF expressions provide an intuitive index number which is operational with Computable General Equilibrium models. The theoretical analysis and an application to Korean data in 1963 both cast doubt on the desirability of tariff cuts in convex competitive economies with active government budget constraints.